Relevancy Trumps Format When Teaching Information Literacy - Badia, Giovanna (Evidence Based Library and Information Practice, 2014)
A Review of: Tewell, E. C. (2014). Tying television comedies to information literacy: A mixed-methods investigation. The Journal of Academic Librarianship, 40(2), 134-141. doi:10.1016/j.acalib.2014.02.004 Abstract Objective – This study assessed the effects of showing television comedy clips to demonstrate information literacy concepts when teaching one-shot instruction sessions. More specifically, it examined whether the students’ retention and understanding increased when television comedy clips were used and whether students preferred instruction that included popular culture examples. Design – A mixed-methods investigation that employed multiple-choice questionnaires and focus group interviews. Setting – A small liberal arts college in the United States of America. Subjects – A total of 211 freshmen students enrolled in a First-Year Studies course. The students were divided into 16 class sections. The author collected a total of 193 valid responses to the pretests and posttests in his study. Methods – Half of the class sections (103 respondents) were taught selected information literacy concepts using television comedy clips and a group discussion led by the instructor. The other half (90 respondents) were taught using only an instructor-led discussion. The classes were randomly selected to belong to the experimental group (with TV comedy clips) or the control group (without TV comedy clips). An online pretest questionnaire, consisting of 10 multiple-choice questions, was administered at the beginning of the 90-minute library instruction session for both groups. An online posttest questionnaire, consisting of the same questions as the pretest but in a randomized order, was completed by the students at the end of the session. About a month later, one-hour focus group interviews were conducted with a small subset of the study’s subjects who volunteered to participate in the focus groups. The experimental focus group consisted of five study participants who had attended a library instruction session that involved showing the television comedy clips and the control focus group consisted of six study participants who had attended a library instruction session that did not include showing the television comedy clips. Main Results – The experimental group scored higher than the control group on the posttest with an average “increase of 1.07 points from pre- to posttest compared to a 0.13 mean increase in the control group” (p. 139), which means that the experimental group answered one more question correctly. Four out of the five participants in the experimental focus group also discussed the television comedy clips even though they were not asked about them. Conversely, when asked about what they enjoyed in the class, the majority of participants from both focus groups discussed the content covered in the session rather than any teaching methods employed. “The quantitative results suggest that student test results either increased, as in the experimental group, or remained relatively level, as in the control group, due to the type of instruction received” (p. 137). Conclusion – The author states that the results from the test questionnaires and answers from focus group sessions indicate that using television comedy clips may be a successful way of improving students’ retention of course content. However, the study’s results could not demonstrate that students liked classes with popular culture examples more than classes without them, since the majority of focus group participants found the course content more interesting than the manner in which the content was taught. The relevancy of the content presented in an information literacy session appears to make more of an impact on the students than the format in which it is presented.